The prognostic value of sarcopenia combined with hepatolithiasis in intrahepatic cholangiocarcinoma patients after surgery: A prospective cohort study. (March 2021) - Deng, Liming; Wang, Yi; Zhao, Jungang; Tong, Yifan; Zhang, Sina; Jin, Chen; Chen, Kaiyu; Bao, Wenming; Yu, Zhengping; Chen, Gang
Abstract: Introduction: Intrahepatic Cholangiocarcinoma (ICC) is the second most common primary liver cancer with dismal survival rates. This study aimed to explore the prognostic value of sarcopenia combine with hepatolithiasis in surgically treated ICC patients and develop a prognostic nomogram to help make clinical decisions. Materials and methods: A prospective cohort study was conducted including patients who underwent hepatectomy for ICC between August 2012 and October 2019. The association between the sarcopenia combined with hepatolithiasis and survival, including overall survival (OS) and recurrence-free survival (RFS) was investigated using the Kaplan-Meier (K-M) method. Univariable and multivariable Cox regression analysis was performed to determine the independent prognostic factors and a nomogram establishment was undertaken based on the multivariable analysis. Results: A total of 121 ICC patients were included in the study. K-M analysis revealed that ICC patients with sarcopenia and hepatolithiasis have worse OS and RFS than those without sarcopenias and/or hepatolithiasis ( p  < 0.01). Multivariable analysis showed that age, serum CEA, hepatolithiasis, sarcopenia and diabetes were independent prognostic factors for OS( p  < 0.05). Finally, a nomogram with good performance in survival prediction was established (C-index was 0.721; the area under the curve of OS was 0.837). The stratified analysis based on the nomogram disclosed that the median OS was 11.9 months in high-risk patients and 51.2 months in low-risk patients ( p  < 0.001). Conclusions: ICC patients with sarcopenia and hepatolithiasis have worse OS and RFS. The nomogram we developed is a practical tool that can provide a more individualized risk assessment for surgically treated ICC patients.